Surface markers versus clusters for determining lower limb joint kinematics in sprint running - Exell, T.; Kerwin, D.; Irwin, G.; Gittoes, M. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purpose of this study was to compare lower limb joint angle time histories using surface markers and segmental clusters. An athlete completed three single leg standing trials whilst moving the joints of the free leg from maximum flexion to maximum extension followed by seven maximal sprint runs. Trials were tracked by a three-dimensional CODA system. For standing trials, mean timing differences were greatest in maximum extension at the ankle and hip (0.01 s). Angle differences ranged from 2° (knee flexion) to 11° (ankle extension). Timing differences in sprinting were greatest in extension (hip 0.03 s) with joint angle differences in maximum flexion and extension 7 & 9° (ankle), 3 & 6° (knee) and 23 & 4° (hip) respectively. When comparing results from surface markers and clusters, a good level of agreement was found in the continuous knee flexion-extension profile, and the discrete timings for all joints.